2020
DOI: 10.3390/pathogens9060481
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of and Barriers to the Development of Epitope-Based Vaccines against Human Metapneumovirus

Abstract: Human metapneumovirus (HMPV) is a major cause of respiratory illnesses in children, the elderly and immunocompromised patients. Although this pathogen was only discovered in 2001, an enormous amount of research has been conducted in order to develop safe and effective vaccines to prevent people from contracting the disease. In this review, we summarize current knowledge about the most promising experimental B- and T-cell epitopes of human metapneumovirus for the rational design of HMPV vaccines using vector de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 105 publications
(157 reference statements)
0
5
0
Order By: Relevance
“…However, reinfections among the immunocompromised and older adults can lead to more severe disease such as bronchiolitis and pneumonia (Boivin et al, 2002(Boivin et al, , 2007Walsh et al, 2008). Although vaccines and monoclonal antibodies are in various stages of early clinical development (Biacchesi et al, 2005;Chupin et al, 2021;Cox et al, 2014;Cseke et al, 2007;Hamelin et al, 2007;Herfst et al, 2008;Huang et al, 2021;Karron et al, 2018;Levy et al, 2013;Olmedillas et al, 2018;Schuster et al, 2015;Stepanova et al, 2020;Stewart-Jones et al, 2021), there are currently no US FDA-approved interventions available. To develop an effective hMPV countermeasure, it will be important to have a thorough understanding of the humoral immune response that is elicited by natural infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, reinfections among the immunocompromised and older adults can lead to more severe disease such as bronchiolitis and pneumonia (Boivin et al, 2002(Boivin et al, , 2007Walsh et al, 2008). Although vaccines and monoclonal antibodies are in various stages of early clinical development (Biacchesi et al, 2005;Chupin et al, 2021;Cox et al, 2014;Cseke et al, 2007;Hamelin et al, 2007;Herfst et al, 2008;Huang et al, 2021;Karron et al, 2018;Levy et al, 2013;Olmedillas et al, 2018;Schuster et al, 2015;Stepanova et al, 2020;Stewart-Jones et al, 2021), there are currently no US FDA-approved interventions available. To develop an effective hMPV countermeasure, it will be important to have a thorough understanding of the humoral immune response that is elicited by natural infection.…”
Section: Introductionmentioning
confidence: 99%
“… 52 , 53 Meanwhile, most identified epitopes are located on F protein, the use of the F protein alone can induce the production of protective monoclonal antibodies, while currently no other proteins have been found to generate neutralizing antibodies. 54 , 55 However, proteins other than F are also involved in immune response, SH can inhibit the secretion of inflammatory cytokines, while G protein has the ability to decrease innate immune responses. Although viruses lacking G and SH proteins can still replicate, their replication efficiency will be greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that many HMPV vaccines exhibit immune damage problems, such as enhanced disease and delayed viral clearance due to excessive activation of Th2-type immune responses in animal experiments( Schickli et al, 2009 ; Anderson, 2013 ; Aerts et al, 2015 ). In our study, we evaluated recombinant virus-induced immune response phenotypes by some popular representative factors of Th1-type and Th2-type immune responses( Dubois et al, 2019 ; Stepanova et al, 2020 ). rFLU-HMPV/F-NS activated Th1/Th2 type immune responses in vivo and favored Th1 type cellular immune responses, inducing a Th1/Th2 type balance.…”
Section: Discussionmentioning
confidence: 99%
“…An effective HMPV vaccine would ensure the induction of a prompt and appropriate immune response (generation of immune memory) following natural HMPV infection of the host ( Herd et al, 2006 ; Ren et al, 2015 ). Accurate stimulation of CD4 T cells to increase antibody production following vaccine immunization and the formation of a rapid and effective secondary CTL response of CD8 memory T cells to natural HMPV infection are key issues in the study of effective HMPV vaccines ( Hamelin et al, 2007 ; Kolli et al, 2008 ; González et al, 2017 ; Stepanova et al, 2020 ). Therefore, studying the CD4 branch of HMPV immunity is a key requirement for controlling the pathological process of HMPV and developing prevention strategies.…”
Section: Discussionmentioning
confidence: 99%